2015
DOI: 10.1371/journal.pone.0120851
|View full text |Cite
|
Sign up to set email alerts
|

Smad4 Loss Synergizes with TGFα Overexpression in Promoting Pancreatic Metaplasia, PanIN Development, and Fibrosis

Abstract: AimsWhile overexpression of TGFα has been reported in human pancreatic ductal adenocarcinoma (PDAC), mice with overexpressed TGFα develop premalignant pancreatic acinar-to-ductal metaplasia (ADM) but not PDAC. TGF-β signaling pathway is pivotal to the development of PDAC and tissue fibrosis. Here we sought to investigate the interplay between TGFα and TGF-β signaling in pancreatic tumorigenesis and fibrosis, namely via Smad4 inactivation.MethodsThe MT-TGFα mouse was crossed with a new Smad4 conditional knock-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
2
16
0
1
Order By: Relevance
“…ADM was reproduced experimentally, in a caerulein‐induced pancreatitis mouse model, and in multiple transgenic mouse models (Grabliauskaite et al, ; Guerra et al, ; Lowenfels & Maisonneuve, ). Metaplastic duct cells are more likely accumulate gene mutations leading to cell cycle disruption, loss of tumor suppressor and DNA repair genes and to progress to pancreatic intraepithelial neoplasia (PanIN) first and invasive PDAC later (Garcia‐Carracedo et al, ; Shi et al, ). Many cytokines and activated signaling pathways may drive ADM in the inflammatory microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADM was reproduced experimentally, in a caerulein‐induced pancreatitis mouse model, and in multiple transgenic mouse models (Grabliauskaite et al, ; Guerra et al, ; Lowenfels & Maisonneuve, ). Metaplastic duct cells are more likely accumulate gene mutations leading to cell cycle disruption, loss of tumor suppressor and DNA repair genes and to progress to pancreatic intraepithelial neoplasia (PanIN) first and invasive PDAC later (Garcia‐Carracedo et al, ; Shi et al, ). Many cytokines and activated signaling pathways may drive ADM in the inflammatory microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…ADM was reproduced experimentally, in a caerulein-induced pancreatitis mouse model, and in multiple transgenic mouse models (Grabliauskaite et al, 2015;Guerra et al, 2007;Lowenfels & Maisonneuve, 2006). Metaplastic duct cells are more likely accumulate gene mutations leading to cell cycle disruption, loss of tumor suppressor and DNA repair genes and to progress to pancreatic intraepithelial neoplasia (PanIN) first and invasive PDAC later (Garcia-Carracedo et al, 2015;Shi et al, 2009) showed that TNFα is overexpressed in pancreatitis and could induce ADM in acinar cells through NF-κB activation (Liou et al, 2013). Further, tumor cell-and macrophage-derived TNFα plays a profound role in pancreatitis and pancreas malignancy, and inhibition of TNFα had a protective effect (Egberts et al, 2008;Hughes et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It occurs in 6-12 patients in 100,000 per year in the United States [1][2][3]. With advancing age, the risk of PDAC increases and the median age of diagnosis is 71 years [1].…”
Section: Introductionmentioning
confidence: 99%
“…Согласно недавно проведенному исследованию, снижение активности SMAD-4 с чрезмерным повышением показателей TGF-α приводило к развитию фиброзных изменений в ткани поджелудочной железы [8]. Повышение активности TGF-β1 при воспалительных изменениях поджелудочной железы сопровождается нарушением регуляции микро РНК-217-SIRT1 с усилением развития фиброза в под желу доч ной железе [7].…”
Section: трансформирующий фактор роста β ассоциированный с белком кunclassified